2017
DOI: 10.1155/2017/8493145
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Lifestyle Adaptation for the Prevention of Prediabetes in Adults: A Systematic Review

Abstract: Diabetes prevalence is increasing exceptionally worldwide and with this come associated healthcare costs. The primary outcome of this systematic review was to assess glycaemic control and incidence of Type 2 diabetes mellitus (T2DM) diagnosis after exercise and dietary intervention (measured with any validated scale). The secondary outcome assessed body mass index change, weight change, and physical exercise capacity after diet and exercise intervention (measured with any validated scale). 1,780 studies were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 46 publications
0
49
0
10
Order By: Relevance
“…It does not meet the criteria for T2DM, but individuals with prediabetes have an increased risk of developing both T2DM and cardiovascular disease . However, of note is the fact that maintaining the glycemic index under control and performing physical exercise could be effective in delaying or preventing the progression of prediabetes to T2DM . Therefore, a comprehensive health checkup with lifestyle education and doctor's consultation are useful ways to prevent T2DM development in prediabetes patients …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It does not meet the criteria for T2DM, but individuals with prediabetes have an increased risk of developing both T2DM and cardiovascular disease . However, of note is the fact that maintaining the glycemic index under control and performing physical exercise could be effective in delaying or preventing the progression of prediabetes to T2DM . Therefore, a comprehensive health checkup with lifestyle education and doctor's consultation are useful ways to prevent T2DM development in prediabetes patients …”
mentioning
confidence: 99%
“…3 However, of note is the fact that maintaining the glycemic index under control and performing physical exercise could be effective in delaying or preventing the progression of prediabetes to T2DM. 4 Therefore, a comprehensive health checkup with lifestyle education and doctor's consultation are useful ways to prevent T2DM development in prediabetes patients. 5 Pancreatic fibrosis is a representative pancreatic feature in patients with impaired glucose tolerance (IGT).…”
mentioning
confidence: 99%
“…This is especially important when the lifestyle adaptation can prevent the complications of DMT2 [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, although the Da Qing study indicated the effectiveness of lifestyle intervention (LSI), ~44% of participants in the LSI groups still developed diabetes, and the median delay in diabetes onset in the intervention group was 4 years compared with the control group . A recent systematic review of lifestyle adaptation to prevent diabetes also indicated that, while the cumulative incidence of diabetes could be drastically decreased in the short term, problems with adherence meant that improvements diminished over time …”
Section: Introductionmentioning
confidence: 99%
“…12 A recent systematic review of lifestyle adaptation to prevent diabetes also indicated that, while the cumulative incidence of diabetes could be drastically decreased in the short term, problems with adherence meant that improvements diminished over time. 13 For these and other reasons, LSI is often combined with pharmacological interventions for increased benefits. Pharmacological agents, such as metformin, 8,14 troglitazone 15,16 and acarbose, 14,17 have also been found to be effective in decreasing the rate of progression from IGR to diabetes.…”
mentioning
confidence: 99%